The Influence Of Education At Postpartum Visits On The Knowledge And Attitude Of Mothers About Postpartum Danger Signs - Tri Ambarsari, Dela; Putri, Rismaina; Fransiska, Ratna Diana; Silvani, Yulia (Universitas Islam Jember, 2023)
Indonesia's MMR is ranked 3rd highest in Southeast Asia. The postpartum period is the most common cause of maternal death in Indonesia. Data obtained in 2021, as much as 40% during postpartum or postpartum. This study aims to determine the effect of education during postpartum visits on mothers' knowledge and attitudes about postpartum danger signs at the Slahung Ponorogo Health Center. Preexperimental research design with a one group pretest posttest design approach. The sample in this study were part of the postpartum mothers who were in the working area of the Slahung Ponorogo Health Center. Sampling using purposive sampling method a number of 44 respondents. The results showed that there was an effect of education during postpartum visits on the knowledge and attitudes of mothers about the danger signs of the puerperium with a significant value of 0.000 <0.05. Thus, it can be concluded that education during postpartum visits influences the knowledge and attitudes of postpartum mothers so that if mothers ind any of the danger signs of child birth they can immediately have them checked by medical personnel so that complications can be prevented.